Subacute granulomatous (De Quervain) thyroiditis mimicking thyroid malignancy on ultrasonography: Fine-needle aspiration cytology preventing an unnecessary thyroidectomy - Manchikalapudi, Sai Kaushal; Warpe, Bhushan M.; Joshi, Shweta S. (Indian Journal of Case Reports, 2026)
Subacute granulomatous thyroiditis (De Quervain thyroiditis) is a self-limiting inflammatory disorder characterized by painful thyroid enlargement, fever, and elevated inflammatory markers. While its clinical presentation is often distinctive, ultrasonographic (USG) findings can occasionally simulate thyroid malignancy, specifically mimicking infiltrative neoplasms with irregular margins and hypoechoic areas, leading to diagnostic uncertainty. This report details the case of a 30-year-old woman who presented with acute painful neck swelling and thyrotoxicosis. USG revealed heterogeneous solid lesions with irregular margins, classified as Thyroid Imaging Reporting and Data System 4, raising significant suspicion of malignancy. Fine-needle aspiration cytology (FNAC) proved crucial, demonstrating characteristic epithelioid granulomas and multinucleated giant cells, thereby confirming the diagnosis of subacute thyroiditis and averting an unnecessary thyroidectomy. This case underscores the indispensable role of FNAC in resolving diagnostic dilemmas where radiological findings are misleadingly suggestive of malignancy